Intellectual Capital, Technological Intensity and Firm Performance: The Case of Emerging Countries - AYBARS, ASLI; AVCI, EMİN; ÖNER, MEHTAP; ÇİNKO, MURAT (ALEXANDRU IOAN CUZA UNIV IASI FAC ECONOMICS & BUSINESS ADM, 2021)
While neglecting the importance of technological intensity, most of the prior studies documented the positive contribution of intellectual capital (IC) to corporate financial performance. This study aims at analyzing the relation between IC and corporate financial performance addressing the technological intensity in different sectors from 17 emerging countries. The impact of IC, which is measured by Value Added Intellectual Coefficient (VAIC) and its components; Capital Employed Efficiency (CEE), Human Capital Efficiency (HCE), and Structural Capital Efficiency (SCE), on corporate financial performance will be evaluated using panel data analysis for the period between 2009-2019. Accordingly, IC and its components are found to be significant drivers of financial performance being higher for sectors that are more technology intensive. Moreover, human and physical capital are the main components, which boost finance performance for all groups irrespective of technological intensity in the emerging market context.
Keywords: emerging markets; Value Added Intellectual Coefficient; technological intensity; financial performance; panel data; FINANCIAL PERFORMANCE; EMPIRICAL-EVIDENCE; MARKET VALUE; IMPACT; STOCK